Rancang Bangun Alat Ukur Jarak dan Peringatan pada Visual Docking Guidance System menggunakan Sensor Lidar - Sidiq Wijanarko; Catur Budi Waluyo; Denny Dermawan (Institut Teknologi Dirgantara Adisutjipto, 2019)
The limited ground marshall, yellow line and others at an airport will affect when parking aircraft. Aviation technology has provided solutions, among others, by attaching to aircraft equipment known as the Visual Docking Guidance System (VDGS), is a tool provided by the airport to help a pilot park his plane without the help of a marshaller to direct the movement of planes to the correct parking. However, not all airports are equipped with sophisticated equipment. So this research aims to create a system that can make it easier for pilots to park aircraft while in Apron. To overcome this problem, a VDGS tool was designed which was designed using a TF Mini Lidar sensor and programmed for aircraft parking systems at pioneering airports. This tool is able to provide information on the distance of the plane as far as 12 meters given a condition that the aircraft will display identification of guidance or collision prevention that will STOP if the aircraft is at a distance of 1-3 meters, and GO identification if the aircraft is at a distance of 4-12 meters so that this tool can serves as a guide to the position of the aircraft when parking right in the designated parking area and prevent aircraft crashes when parking when entering the apron area at the pioneer airport.